The Aesthetic Hyper-Object in Experimental Short Film Practices: Lina Sieckmann and Miriam Gossing’s Art Documentaries (Konturen, 2022)
Short experimental films by the German female director duo Lina Sieckmann und Miriam Gossing put domestic environments on cinematic display in new and challenging ways. The essay discusses the links between the films’ documentary agendas, surreal visual montages, and poetic feminine voice-overs. Selected films are placed into dialogues with Michael Renov’s concept of aesthetics in documentary film and Timothy Morton’s notion of the “hyperobject.” This theoretical framework highlights the tensions between the films’ powerful aesthetics and feminine queer desire as they decenter socially ingrained dualisms.